PERSIAPAN SDM UNGGUL MEMALUI PEMBELAJARAN RASA, KARSA, CIPTA DAN KARYA DALAM PENDIDIKAN ERA REVOLUSI 4.0 DI SMK NEGERI 8 PALEMBANG - Hendri Gunawan; Diana Widhi Rachmawati; Neta Dian Lestari; Masnunah; Erma Yulaini; Nova Pratiwi; Chandra Kurniawan; Januardi; Boby Agus Yusmiono (Bajang Institute, 2021)
The methods used in Community Service activities are: lectures, questions and answers, discussions at SMK Negeri 8 Palembang. The theme raised was